2014
DOI: 10.3233/npm-14814010
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarkers and echocardiographic indices of left ventricular function in very low birth weight infants

Abstract: OBJECTIVE: Evaluate plasma markers of myocardial function and ischemia [B-type natriuretic peptide] (BNP) and cardiac troponin T (cTnT)] in relationship to echocardiographic indices of left ventricular (LV) function and severity of illness score (SNAPPE-II) in Very-Low-Birth-Weight-Infants (VLBWIs) prospectively. STUDY DESIGN: Serial echocardiography studies, clinical data, BNP and cTnT were obtained in thirty VLBWIs on postnatal days 1, 2, 3 and 7. RESULTS: BNP increased and cTnT decreased significantly day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
2
1
3
Order By: Relevance
“…According to the clinical presentation and echocardiography findings, preterm neonates were divided into the case (with arterial diameter>1.5 mm) [12] and control (without PDA) groups. All eligible subjects entered the study until the number of participants reached the proposed sample size for each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the clinical presentation and echocardiography findings, preterm neonates were divided into the case (with arterial diameter>1.5 mm) [12] and control (without PDA) groups. All eligible subjects entered the study until the number of participants reached the proposed sample size for each group.…”
Section: Methodsmentioning
confidence: 99%
“…These findings have proposed cTnT as a biomarker that may show the presence of PDA, its responses to treatment, and closure [9]. On the other hand, other studies demonstrated that the level of cTnT in preterm neonates was correlated to the presence of PDA or the size of PDA diameter [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Os valores da cTnTcordão observados em nossa casuística foram mais altos que aqueles observados pelos autores citados 23,35,36,42,45,46,49 , e próximos aos encontrados por Fortunato et al 50 em 22 fetos de 20 a 25 semanas submetidos a cordocentese (mediana de 0,174 ng/mL, percentil 99 de 0,308 ng/mL). Embora vários autores tenham afirmado que não há correlação entre cTnTcordão ou cTnT e idade gestacional 23,37,47,49,[51][52][53] , constatamos correlação negativa entre cTnTcordão e idade gestacional.…”
Section: Discussionunclassified
“…Assim como outros autores que estudaram a associação entre hipotensão e cTnTcordão ou cTnT durante as primeiras 48 horas de vida em recém-nascidos asfixiados 55 e com síndrome do desconforto respiratório 51,52 , não encontramos associação entre hipotensão e cTnTcordão. Por outro lado, já foi descrita associação entre cTnT e uso de inotrópico em recém-nascidos de termo asfixiados com 12 horas de vida 58 , em recém-nascidos pré-termo com síndrome do desconforto respiratório 20,41,52 ou com persistência do canal arterial 53 No nosso estudo, a única medida ecocardiográfica que mostrou correlação com cTnTcordão foi FEVE, uma medida reprodutível e de fácil obtenção, mas incompleta se utilizada isoladamente, pois apenas avalia a função ventricular no sentido circunferencial, sem levar em consideração o eixo longitudinal 28 . Além disso, não observamos associação entre o valor de cTnTcordão e a presença de disfunção cardíaca.…”
Section: Discussionunclassified
“…No entanto, alguns estudos demonstram o aumento de cTnT em neonatos com disfunção cardíaca em diversas doenças 85 . Perugu S. et al85 verificaram, em estudo prospectivo, aumento da expressão da cTnT em neonatos de muito baixo peso (MBP) proporcionalmente à severidade da doença. Sadoh W. et al encontraram altos níveis plasmáticos de cTnT em neonatos com asfixia perinatal grave e correlacionaram com injúrias cardiomiocíticas.São diversos os estudos correlacionando os altos níveis de cTnT no plasma com a insuficiência ou injúria cardíaca neonatal86,87,88 , ainda que esta esteja correlacionada apenas com a hemodinâmica do neonato.…”
unclassified